Comparative study on the pyrolysis behavior and pyrolysate characteristics of Fushun oil shale during anhydrous pyrolysis and sub/supercritical water pyrolysis. Issue 26 (1st June 2022) - Lu, Yang; Wang, Zhijing; Kang, Zhiqin; Li, Wei; Yang, Dong; Zhao, Yangsheng
Abstract : Sub/supercritical water can directly extract oil and gas from oil shale due to the solvent and driving effects. Also, they can be considered as an acid–base catalyst, which can catalyze some reactions such as hydrolysis, addition and rearrangement. Abstract : Injected steam can be converted to the sub/supercritical state during the in situ exploitation of oil shale. Thus, the pyrolysis behavior and pyrolysate characteristic of Fushun oil shale during anhydrous pyrolysis and sub/supercritical water pyrolysis were fully compared. The results revealed that the discharged oil yields from sub/supercritical water pyrolysis were 5.44 and 14.33 times that from anhydrous pyrolysis at 360 °C and 450 °C, which was due to the extraction and driving effect of sub/supercritical water. Also, sub/supercritical water could facilitate the discharge and migration of shale oil from the pores and channels. The H2 and CO2 yields in sub/supercritical water pyrolysis were higher than that in anhydrous pyrolysis, resulting from the water–gas shift reaction. The component of shale oil was dominated by saturated hydrocarbons in anhydrous pyrolysis, which accounted for 50–65%. In contrast, a large amount of asphaltenes and resins was formed during pyrolysis in sub/supercritical water due to the solvent effect and weak thermal cracking. The shale oil from anhydrous pyrolysis was lighter than that from sub/supercritical water pyrolysis. Sub/supercritical water reduced the geochemical characteristic indices and lowered the hydrocarbon generation potential and maturity of solid residuals, which can be attributed to the fact that more organic matter was depolymerized and released. The pyrolysate characteristic of oil shale in sub/supercritical water pyrolysis was controlled by multiple mechanisms, including solvent and driving effect, chemical hydrogen-donation and acid–base catalysis.